Antagonistic Activity of Endophytic Bacterial Consortia Against Helminthosporium oryzae Breda de Haan, The Causal Agent of Brown Spot Disease in Rice - Resti, Zurai; Nurbailis, Nurbailis; Fauzia, Afifa (CROPSAVER, 2025)
Helminthosporium oryzae is a pathogen responsible for rice damage and losses of up to 45%. A consortium of endophytic bacteria as a biological agent is one of alternative and eco-friendly ways to suppress the development of plant pathogenic fungi. This research aimed to obtain an endophytic bacterial consortium capable of inhibiting the growth of H. oryzae. This research used a Completely Randomized Design (CRD) to investigate the efficacy of a consortium of six endophytic bacteria, alongside a control group, with three replications. The treatments included A (control), B (Serratia marcescens ULG1E4; Serratia marcescens JB1E3), C (Bacillus sp. HI; Serratia marcescens JB1E3), D (Bacillus sp. HI; Bacillus sp. SJI; Serratia marcescens JB1E3), E (Serratia marcescens ULG1E4; Serratia marcescens JB1E3; Serratia marcescens JB1E2), F (Bacillus sp. HI; Bacillus sp. SJI), and G (Bacillus sp. SJI; Serratia marcescens ULG1E4). The ability of endophytic bacterial consortia to suppress the growth of H. oryzae was evaluated utilizing dual culture and poisoned media techniques. The parameters observed were the inhibitory capacity of endophytic bacterial consortia, the inhibitory potential of secondary metabolites produced by the endophytic bacterial consortia, as well as the fresh weight and dry weight of the fungus. The results showed that treatment G (Bacillus sp. SJI; Serratia marcescens ULG1E4), B (S. marcescens ULG1E4; Serratia marcescens JB1E3), and E (Serratia marcescens ULG1E4; Serratia marcescens JB1E3; Serratia marcescens JB1E2), had a high ability to suppress the growth of H. oryzae with suspension inhibition 61,28%, 62,93%, 63,55%, and secondary metabolites inhibition rates of 96,93%, 94,21%, 97,60%.